2017
DOI: 10.1186/s12884-017-1326-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care quality in near miss and maternal mortality in an academic public tertiary hospital in Yogyakarta, Indonesia: a retrospective cohort study

Abstract: BackgroundReducing maternal mortality remains a major challenge for health care systems worldwide. The factors related to maternal mortality were extensively researched, and maternal death clusters around labour, delivery and the immediate postpartum period. Studies on the quality of maternal care in academic medical centre settings in low income countries are uncommon.MethodsA retrospective cohort study of maternal deaths was conducted in an academic public tertiary hospital in Yogyakarta, and maternal near m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
3
27
0
4
Order By: Relevance
“…Only 29.4% of maternal deaths occurred at the home. Several studies have suggested that poor quality of maternal care at health facilities in Indonesia contributes to high maternal mortality . A study in Papua province suggests poor quality and delays in receiving appropriate care at facilities are the major causes of maternal mortality …”
Section: Introductionmentioning
confidence: 99%
“…Only 29.4% of maternal deaths occurred at the home. Several studies have suggested that poor quality of maternal care at health facilities in Indonesia contributes to high maternal mortality . A study in Papua province suggests poor quality and delays in receiving appropriate care at facilities are the major causes of maternal mortality …”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, as in Indonesia, the most common causes of maternal mortality are postpartum hemorrhage, hypertensive disorders, prolonged labor, complications from unsafe abortion and infection. The risks of maternal near miss and mortality are highest during labor, delivery and the immediate postpartum period 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Sehingga diperlukan sistem rujukan yang tepat untuk mencegah kematian ibu. 4 maternal, disertai dengan risiko lain seperti tempat melahirkan di fasilitas sekunder, multiparitas dan adanya riwayat keguguran sebelumnya. 5 Penelitian yang dilakukan di RSUP dr. Sardjito Yogyakarta sebelumnya menunjukkan bahwa ibu yang meninggal atau nyaris meninggal di RSUP dr. Sardjito sebagian besar merupakan pasien rujukan dari fasilitas perawatan kesehatan lainnya (OR 0,09; 95% CI 0,01-0,91).…”
Section: Pendahuluanunclassified
“…Hal ini disebabkan keadaan umum yang buruk saat pasien dirujuk dan keterlambatan dalam merujuk. 4 Pada penelitian ini kasus-kasus rujukan berpengaruh secara signifikan terhadap kejadian kematian maternal (OR=11,67; 95% CI 4,51-30,2). Hal ini disebabkan ibu yang dirujuk dari fasilitas kesehatan lain, dengan kondisi umum ibu yang mengalami komplikasi kelahiran yang berat, keterlambatan merujuk dan keterlambatan mengenali kasus maternal dengan kegawatan obstetrik pada rumah sakit di bawah level tersier.…”
Section: Pendahuluanunclassified